Splice-Switching Antisense Oligonucleotides Reduce LRRK2 Kinase Activity in Human LRRK2 Transgenic Mice - Joanna A. Korecka; Ria Thomas; Anthony J. Hinrich; Alyssa M. Moskites; Zach K. Macbain; Penelope J. Hallett; Ole Isacson; Michelle L. Hastings (Molecular Therapy: Nucleic Acids, 2020)
Parkinson’s disease (PD) is a progressive neurological disorder estimated to affect 7–10 million people worldwide. There is no treatment available that cures or slows the progression of PD. Elevated leucine-rich repeat kinase 2 (LRRK2) activity has been associated with genetic and sporadic forms of PD and, thus, reducing LRRK2 function is a promising therapeutic strategy. We have previously reported that an antisense oligonucleotide (ASO) that blocks splicing of LRRK2 exon 41, which encodes part of the kinase domain, reverses aberrant endoplasmic reticulum (ER) calcium levels and mitophagy defects in PD patient-derived cell lines harboring the LRRK2 G2019S mutation. In this study, we show that treating transgenic mice expressing human wild-type or G2019S LRRK2 with a single intracerebroventricular injection of ASO induces exon 41 skipping and results in a decrease in phosphorylation of the LRRK2 kinase substrate RAB10. Exon 41 skipping also reverses LRRK2 kinase-dependent changes in LC3B II/I ratios, a marker for the autophagic process. These results demonstrate the potential of LRRK2 exon 41 skipping as a possible therapeutic strategy to modulate pathogenic LRRK2 kinase activity associated with PD development.